Aerospace series. Heat resisting alloy NI-PH2801 (NiCr16Fe7Ti3Nb1Al1). Consumable electrode remelted. Cold drawn wire for the manufacture of thread inserts. D ≤ 3 mm. (16th December 2019) - British Standards Institution,
No abstract available